Selenium Concentrations in Forages of a Northern Herbivore - Shaw, George G.; Reynolds, Hal W. (ARCTIC, 1985)
The importance of adequate selenium in diets of native wild herbivores can only be inferred from data for beef cattle where minimum dietary concentrations range from 50 to 100 ppb. Concern about possible selenium deficiencies in wild herbivores is based on a few reports of symptoms in wildlife, a paucity of data on selenium in their forages, and the idea that excessive atmospheric sulfur may increase the incidence of selenium deficiencies in herbivores. Concentrations of selenium in sedges, Carex spp., and reedgrasses, Calamagrostis spp., the main food plants of bison, Bison bison, in northwestern Canada, varied from 9 to 800 ppb in samples collected at three lowlands locations. However, approximately three-quarters of all the samples of plant species consumed by bison were dietarily deficient by the beef cattle standard.Key words: Carex, Calamagrostis, bison, selenium concentration Mots clés: Carex, calamagrostis, bison, concentration de sélénium